FLIPPED CLASSROOM EN EL DESARROLLO DE PENSAMIENTO CRÍTICO EN LOS ESTUDIANTES DE LA CARRERA DE PSICOLOGÍA, DE LA UNIVERSIDAD TÉCNICA DE BABAHOYO. - LOZANO SANCHEZ CARMEN (2024)
In itself, the flipped classroom, or inverted classroom, is a pedagogical approach that inverts the traditional teaching model. In this method, students study concepts at home through multimedia materials, such as videos or readings, and then participate in hands-on and discussion activities in the classroom. This methodology promotes more active and student-centered learning, allowing more time in class for the practical application of concepts and interaction between students and the teacher. Regarding its influence on critical thinking, the flipped classroom offers several opportunities to develop this skill. By reversing class time, students have the opportunity to process information on their own before discussing it in class. This encourages individual reflection and questioning, which in turn promotes critical thinking. Additionally, by participating in hands-on and discussion activities in class, students have the opportunity to apply and analyze the concepts learned, further strengthening their critical thinking skills. In summary, the flipped classroom offers a learning environment that promotes critical thinking by allowing students to process information individually before engaging in class activities focused on the application and discussion of concepts. This approach helps students develop analysis, evaluation, and synthesis skills fundamental to critical thinking.